Microvascular Decompression for Trigeminal Neuralgia Secondary to Vertebrobasilar Dolichoectasia: A Case Report and Review of the Literature - Carvalho, Fabiane Caxias de Paula; Cavalcante-Neto, Joaquim Francisco; de Araújo Neto, Francisco Jazon; Matos-Neto, Paulo Roberto; Verde, Lucas Antonissen Lima; Cristino-Filho, Gerardo; Leal, Paulo Roberto Lacerda (Asian Journal of Neurosurgery, 2025)
Vertebrobasilar dolichoectasia (VBD) is a vasculopathy characterized by elongation and dilation of the affected artery. We present a case of trigeminal neuralgia (TN) secondary to VBD, successfully treated with microvascular decompression (MVD) using an autologous muscle graft (AMG). Additionally, we conducted a review of the literature and meta-analysis of 14 studies involving 303 patients to evaluate the efficacy of this surgical approach. A 63-year-old man experienced recurrent, lancinating pain in the V1, V2, and V3 branches of the right trigeminal nerve. Due to the intractable symptoms, he underwent MVD with an AMG after thorough neurological evaluation. At the 1-year follow-up, he was pain-free without the need for further medication. TN secondary to VBD is a rare and challenging condition, often refractory to medical treatment. MVD with an AMG offers significant symptom relief. Further research, including prospective studies or randomized controlled trials comparing AMG with other graft materials, is necessary to confirm its efficacy.
Keywords: microvascular decompression; autologous muscle grafts; trigeminal neuralgia; vertebrobasilar dolichoectasia; systematic review; meta-analysis